Research on Gilead Sciences’ Market Monopolization Strategies and Their Economic Impact on the Global Pharmaceutical Market - Zheng Chunwai (SHS Web of Conferences)
This paper delves into the monopolistic strategies employed by Gilead Sciences, highlighting how these tactics have profound and far- reaching impacts on the pharmaceutical industry. The study examines Gilead’s use of mergers and acquisitions, patent extensions, and aggressive marketing campaigns to secure a dominant market position. Such strategies have not only stifled competition but also contributed to soaring drug prices, placing essential medications out of reach for many individuals. The lack of transparency in this competitive landscape exacerbates the situation, allowing Gilead to maintain its market dominance at the expense of public welfare. Through this research, the paper provides a comprehensive overview of the detrimental effects of monopolistic practices in the pharmaceutical sector, emphasizing the urgent need for regulatory interventions. The study aims to propose viable strategies to dismantle monopolies and promote fair competition, ultimately leading to significant improvements in public health outcomes. These findings contribute to the existing body of knowledge on the intersection between the pharmaceutical industry and public health, offering insights into necessary policy changes and the role of market agents in fostering a more equitable healthcare system.